Self-Efficacies of Prospective Mathematic Teachers’ Technological Pedagogical Content Knowledge (TPACK) - Gaguk Resbiantoro (Jurnal VARIDIKA, 2016)
The purpose of this research was to describe the general self-efficacies of prospective teachers about TPACK; based on gender and the types of internship school. This study was conducted to 55 prospective teachers that had finished their internship program at 18 schools, junior high schools, senior high schools, and vocational high schools. Data were collected through questionnaires, observations, and interviews. Questionnaires consist of statements on each TPACK component with the rating scale of 0-10. The result showed that self-efficacies of each TPACK component are 6,97 for TK, 5,71 for CK; 6,49 for PK; 6,95 for PCK; 6,38 for TCK; 6,05 for TPK; and 5,90 for TPACK; there are significant differences self-efficacies at TK and PCK component between male and female of prospective teachers, with the female one have a higher self-efficacies than the male one; there are significant difference self-efficacies at CK and TPACK component between the prospective teacher that have done an internship program at junior high schools, senior high schools, and vocational high schools.